2013
DOI: 10.1007/s10823-013-9202-9
|View full text |Cite
|
Sign up to set email alerts
|

Border Health in the Shadow of the Hispanic Paradox: Issues in the Conceptualization of Health Disparities in Older Mexican Americans Living in the Southwest

Abstract: Mexican Americans have demonstrated lower than what would be expected mortality rates and disease prevalence, given their overrepresentation among those living in poverty. However, Mexican Americans living along the US-Mexico border have been documented as carrying a higher burden of disease and disability that seems to contradict or at least challenge evidence in support of a “Hispanic Paradox”. The purpose of this paper is to evaluate the concept of border health as it relates to the conceptualization and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…Furthermore, persons coming as immigrants, often with lower human capital, may find themselves at the lower level of the US socioeconomic ladder and become vulnerable to the detrimental consequences of being at that low end. A recent study [21] of diabetes among Mexicans adds support to the above argument which that analysis of diabetes was significantly impacted by income.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Furthermore, persons coming as immigrants, often with lower human capital, may find themselves at the lower level of the US socioeconomic ladder and become vulnerable to the detrimental consequences of being at that low end. A recent study [21] of diabetes among Mexicans adds support to the above argument which that analysis of diabetes was significantly impacted by income.…”
Section: Discussionmentioning
confidence: 80%
“…Some studies have observed what has been termed a "Hispanic paradox" in mortality [17][18][19][20][21]. The paradox is typified by lower all-cause mortality rate for Hispanics compared to their non-Hispanic counterparts.…”
Section: Past Researchmentioning
confidence: 99%
See 3 more Smart Citations